The effectiveness of peer assessment in enhancing cultural tolerance and multicultural competence among vocational high school students - Sai, Servasius; Muhson, Ali; Suswakara, Ignasius (Jurnal Pembangunan Pendidikan: Fondasi dan Aplikasi, 2026)
The current global educational landscape faces the challenge of integrating cultural diversity in the classroom. The phenomena of “ethnicism” and intergroup prejudice often hinder the creation of a conducive learning climate, especially in vocational high schools (SMK), which place great emphasis on technical competency. This study aims to examine the effectiveness of using peer assessment methods in improving cultural tolerance among students at St. Vincentius Ndona Vocational High School. Cultural tolerance in this study is defined as a proactive attitude in appreciating ethnic, religious, and value differences as learning assets. The research method used is a quasi-experiment with a Control Group Pretest-Posttest design. The research subjects were divided into an experimental group that applied peer assessment in the evaluation process and a control group that used traditional evaluation. The research instrument was a cultural tolerance attitude scale that was measured before and after the treatment. The results of this study are expected to provide practical contributions for educators in implementing the Merdeka Curriculum, particularly in the dimension of the Pancasila Student Profile “Global Diversity,” as well as strengthening Catholic education spirituality that upholds human dignity amid diversity. This study aims to examine the effectiveness of peer assessment in improving students’ cultural tolerance attitudes at St. Vincentius Ndona Catholic Vocational School. Amidst the challenges of “sukuisme” and intergroup prejudice, this study uses a quasi-experimental approach with a Control Group Pretest-Posttest design. The research sample consisted of 62 twelfth-grade students divided into an experimental class (n=31) and a control class (n=31). The research instrument was a cultural tolerance attitude questionnaire consisting of 16 valid and reliable statements (0.881). The results showed that the average N-gain of the experimental class was 44.12 (moderate category), which was significantly higher than that of the control class, which was 15.79 (low category). The independent t-test showed a significance value (2-tailed) of 0.043 (p < 0.05), proving that the application of peer assessment was significantly effective in increasing cultural tolerance.